2016
DOI: 10.3390/molecules21101334
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of siRNA to Transferrin Receptor Overexpressing Tumor Cells via Peptide Modified Polyethylenimine

Abstract: Abstract:The use of small interference RNA (siRNA) to target oncogenes is a promising treatment approach for cancer. However, siRNA cancer therapies are hindered by poor delivery of siRNA to cancer cells. Transferrin receptor (TfR) is overexpressed in many types of tumor cells and therefore is a potential target for the selective delivery of siRNA to cancer cells. Here, we used the TfR binding peptide HAIYPRH (HAI peptide) conjugated to cationic polymer branched polyethylenimine (bPEI), optimized the coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The peptides of c(RGD) 2 -9R recognize and interact with integrin by RGD sequence, and provide the ability of targeting to a variety of cancer cells where α v β 3 integrin were overexpressed. Conjugating the carrier with a targeted or functional moiety is a useful and popular strategy for siRNA delivery, and has been validated in many preclinical studies [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peptides of c(RGD) 2 -9R recognize and interact with integrin by RGD sequence, and provide the ability of targeting to a variety of cancer cells where α v β 3 integrin were overexpressed. Conjugating the carrier with a targeted or functional moiety is a useful and popular strategy for siRNA delivery, and has been validated in many preclinical studies [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation of the functions and properties of TfR in iron transport indicate that TfR plays a greater biological role than previously thought . Xie et al reported that H1299 cells demonstrate significantly higher TfR expression compared to A549 and H460 cells . Therefore, we chose to use A549 and H1299 cell lines to locate a TfR overexpressing cell.…”
Section: Discussionmentioning
confidence: 93%
“…5,20,21 Xie et al reported that H1299 cells demonstrate significantly higher TfR expression compared to A549 and H460 cells. 22 Therefore, we chose to use A549 and H1299 cell lines to locate a TfR overexpressing cell. In this study, we observed upregulated protein levels of cellular TfR in lung adenocarcinoma H1299 cells (Fig 1a,b).…”
Section: Discussionmentioning
confidence: 99%
“…The peptide of cyclic (RGD) 2 targeting integrin α ν β 3 was conjugated with 9R, designated as c(RGD) 2 ‐9R. The control peptide of cyclic (GGG) 2 , which did not target any known receptors of tumors, was also conjugated with 9R, designated as c(GGG) 2 ‐9R. All the peptides were synthesized by ChinaPeptides Co, Ltd, China.…”
Section: Methodsmentioning
confidence: 99%